Alat Proteksi Kebakaran Rumah Menggunakan Wemos D1 Mini dengan Alarm dan Notifikasi Email dari Thinger.IO : Home Fire Protection Tool Using Wemos D1 Mini With Alarm and Email Notification from Thinger.IO - Richardo, Helvis (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2022)
Fire is an event that can endanger the life of the owner of the house and cause material loss. In because less serious when dealing with fires. There are many causes of fires, namely the use of non-standard cables that cause electric short circuits, gas leaks, and human negligence such as not being used to light gas stoves. Generally, it is known by the circumstances and environmental conditions around the fire that it starts to grow and quickly rises out of the house, this becomes a problem for the community. The equipment used is to use the internet to display sensor condition information from the Thinger.IO Platform that is connected to the system. This system is made to provide notifications via email and alarms from buzzers to homeowners in real time and can do fire protection by spraying air to reduce fires to become large and losses can be reduced. The test results of the tool can work well, the maximum fire detection sensor is 140 cm. The MQ2 sensor will detect when it exceeds 400 PPM. With email notifications, homeowners can find out the condition of the house, and firefighters can arrive faster because they receive email notifications from fires